Modified CC-PEG Algorithm for Protograph-Based QC-LDPC Codes Over Non-Uniform Channel - Hyeon-Bhin Lee; Jae-Won Kim (IEEE Access)
In this paper, we propose the modified cycle-concentrating progressive-edge-growth (CC-PEG) algorithm for lifting protograph-based quasi-cyclic low-density parity-check (QC-LDPC) codes over the non-uniform additive white Gaussian noise (AWGN) channel. By introducing various selection criteria for shift values based on the non-uniform channel characteristics, we improve the decoding performances of lifted LDPC codes. From numerous simulation results, we demonstrate that each selection criterion is effective for the performance improvement and the modified CC-PEG algorithm outperforms the conventional lifting methods over the non-uniform AWGN channel. Furthermore, we analyze these simulation results based on some metrics such as the girth, number of cycles, and approximate cycle extrinsic message degree (ACE).